So you want to be an entrepreneur? : how to decide if starting a business is really for you - Gillespie-Brown, Jon (Capstone, 2008)
Jon Gillespie Brown brings his extensive mentoring experience to bear in this new handbook for would-be entrepreneurs. So You Want to Be an Entrepreneur? contains a series of mentoring sessions, each carefully thought out to make you consider and plan your life based on your passions, ambitions and ultimate visions. By actively taking part in each of the exercises, you give yourself the best chance of succeeding as an entrepreneur, or the sufficient clarity to decide what other career options are best suited to you. Explore your real goals, hidden talents, passions, assets and core skills.